The Electronic Pharmaceutical Record: A new method for medication reconciliation. Issue 4 (15th May 2018) - Jurado, Camille; Calmels, Violaine; Lobinet, Emilie; Divol, Elodie; Hanaire, Hélène; Metsu, David; Sallerin, Brigitte
Abstract: Rationale, aim, and objective: There are several ways to establish an accurate medication list in the hospital admission medication reconciliation (MedRec). The challenge for MedRec lies in the availability, reliability, and completeness of the data used. In France, the Electronic Pharmaceutical Record (ePR) was developed to register each medication taken by ambulatory patients, primarily to make dispensation in community pharmacies safe. We evaluated the suitability of this tool in the MedRec when patients were admitted to the hospital. Method: We conducted a 6‐month pilot study of 249 MedRec files from a hospital diabetology department. The analysis was supplemented by the ePR for any patient for whom this information was recorded. The study evaluated the ePR as a new MedRec tool, as well as the clinical impact (CI) of the new data collected. Results: The ePR was contributory for 28% of the patients. Discrepancies were associated with polypharmacy, most of which had a CI = 1. Medication omission was the most frequently found discrepancy (72%), but self‐medication (8%) and lack of medication adherence (9%) were also observed. Conclusion: This tool provided added value for reconciliation, as it quickly identifies regular medications, adherence, and self‐medication behaviour. The ePR is essential for conducting a thorough MedRec.